Zerovalent iron and iron(VI): Effective means for the removal of psychoactive pharmaceuticals and illicit drugs from wastewaters - Mackuľak, Tomáš; Birošová, Lucia; Bodík, Igor; Grabic, Roman; Takáčová, Alžbeta; Smolinská, Miroslava; Hanusová, Anna; Híveš, Ján; Gál, Miroslav (The Science of the total environment, 2016)
Herein we report the analysis of 27 selected psychoactive compounds found in the wastewater of the largest suburb in the eastern part of Central Europe Bratislava—Petržalka, Slovakia. Thirteen of them (MDMA, methamphetamine, amphetamine, THC-COOH, benzoylecgonine, codeine, tramadol, venlafaxine, oxazepam, citalopram, methadone, EDDP, cocaine) were found in concentrations above 30 ng/L. These compoundswere selected for further monitoring. The possibility of complete degradation of these 13 substances by zerovalent iron and iron(VI) was studied in thewastewater from the Petržalka treatment plant. During the week the concentration of themajority of the studied compounds inwastewaterwas stable. Concentrations of MDMA, cocaine, tramadol, and oxazepam reached significantly higher levels during the weekend.Only about 10% removal efficiency for tramadol, venlafaxine, oxazepam, MDMA, citalopram, methadone, and EDDP was observed at the treatment plant. In contrast, methamphetamine, amphetamine, and codeine were removed with 68%, 83%, and 53% efficiency, respectively. The degradation of synthetic drugs (methamphetamine, cocaine, MDMA) in wastewater is limited, while cannabis (of natural biological origin) is degradedwith efficiency greater than 90%. After utilization of the Fenton reaction, its modification, and use of ferrate(VI), a high efficiency of eliminating all of these substances to values below the limit of detection was achieved.
Keywords: chemické látky znečišťující vodu; Environmental Monitoring; Illicit drugs; čištění vody; Slovakia; Slovenská republika; Water Purification; monitorování životního prostředí; železo; Fenton-like treatment; odpadní voda; Water Pollutants, Chemical; Waste Water; Psychoactive pharmaceuticals; odpad tekutý - odstraňování; Ferrate(VI); zakázané drogy; Iron; Degradation; Waste Disposal, Fluid; Illicit Drugs; Wastewater